Development of analytical methods for the determination of free and ester bound 2‐, 3‐MCPD, and esterified glycidol in fishery products. Issue 3 (15th June 2015) - Karl, Horst; Merkle, Sybille; Kuhlmann, Jan; Fritsche, Jan
Abstract : In the present study, existing official methods for oils were modified in order to analyze free and bound MCPD and bound glycidol in fish. Free 3‐MCPD was determined in aqueous extracts of fishery products. DGF standard methods C‐VI‐17(10) and C‐VI‐18(10) and the 3 in 1 method were modified and tested to quantify ester‐bound 2‐ and 3‐MCPD and glycidyl esters. The different methods were validated using spiked fish mince and a naturally contaminated reference material consisting of homogenized smoked sprat and fish sticks. The methods showed good agreement. Assay B of the modified DGF method C‐VI‐18(10) and the adapted 3 in 1 method allow a quantitative determination of bound 2‐ and 3‐MCPD in fishery products. In addition, glycidyl esters can be quantified applying the 3 in 1 method. The screening of various fishery products showed that smoked fish may contain considerable amounts of free 3‐MCPD. Concentrations ranged between 8 and 388 μg/kg wet weight (ww). Only traces of free 3‐MCPD were found in all other fishery products. Fish sticks and fried fish products are potential sources of 3‐ and 2‐MCPD esters, but large variation were observed. Bound 3‐MCPD ranged between 45 and 377 μg/kg ww, bound 2‐MCPD between 9 and 116 μg/kg ww. Practical applications: The European Food Safety Authority (EFSA) is calling for occurrence data of 2‐MCPD, 3‐MCPD, 2‐MCPD ester, 3‐MCPD ester, and glycidyl ester in foods including fishery products. At present, there is no official method for the determination of these food processing contaminants in fish and fishery products. Therefore, the approach of this study was to establish analytical methods for the quantification of free and bound MCPD and bound glycidol in fish, based on the modification of existing methods for edible oils. The adapted methods allow a sensitive quantitative determination of the target analytes in various fishery products. The proposed modified methods allow they analysis of free and bound 2‐, 3‐MCPD, and esterified glycidol in fishery products. Abstract : The proposed modified methods allow they analysis of free and bound 2‐, 3‐MCPD, and esterified glycidol in fishery products.